Early Detection and Serotyping of Dengue Viruses Clinical Isolates Using Reverse Transcription Polymerase Chain Reaction (RT-PCR) 2 Primers - Siregar, Abdul Rahman; Wibawa, Tri; Wijayanti, Nastiti (Indonesian Journal of Biotechnology, 2011)
Recently several methods for confirming Dengue Virus have been developed involve virus isolation, detection of virus antigen, and nucleic acid using PCR. It has been reported that rapid detection method for confirming DHF by Multiplex RT-PCR had been successfully developed. It was more effective than the other methods with a high sensitivity and specivicity were 100% at the early phase (day 1-3). This study was designed to develop rapid detection and serotyping methods for Dengue Virus using RT-PCR 2 primers (Dcon and preM) with annealing temperature was 57oC. The whole blood samples were collected from suspected dengue fever patients that had been confirmed with NS1 kit from R.S. Persahabatan DKI Jakarta and R.S. Prof. Dr. Sardjito DI Yogyakarta during Februari-August 2009. The PCR products showed that in 12 samples, 100 % were postitive with different pattern among the serotypes especially for DEN1 and DEN2, but not for DEN3 and Den4.  This method was also able to confirm the double infection DEN2-DEN3, but not for the other ones because of the unspecific pattern. From the results, it indicated that the 2 primers can be a promising early detection and serotyping method of Dengue Virus which infected the DHF patients. Key words: Dengue Virus, DHF, early detection, serotyping, RT-PCR 2 primers.